A crucial active site network of titratable residues guides catalysis and NAD+ binding in human succinic semialdehyde dehydrogenase - Cesaro, Samuele; Orlando, Marco; Bettin, Ilaria; Longo, Carmen; Spagnoli, Giulia; de Laureto, Patrizia Polverino; Molla, Gianluca; Bertoldi, Mariarita (Protein Science, 2025)
Human succinic semialdehyde dehydrogenase is a mitochondrial enzyme fundamental in the neurotransmitter γ-aminobutyric acid catabolism. It catalyzes the NAD+-dependent oxidative degradation of its derivative, succinic semialdehyde, to succinic acid. Mutations in its gene lead to an inherited neurometabolic rare disease, succinic semialdehyde dehydrogenase deficiency, characterized by mental and developmental delay. Due to the poor characterization of this enzyme, we carried out evolutionary and kinetic investigations to contribute to its functional behavior, a prerequisite to interpreting pathogenic variants. An in silico analysis shows that succinic semialdehyde dehydrogenases belong to two families, one human-like and the other of bacterial origin, differing in the oligomeric state and in a network of active site residues. This information is coupled to the biophysical–biochemical characterization of the human recombinant enzyme uncovering that (i) catalysis proceeds by an ordered bi–bi mechanism with NAD+ binding before the aldehyde that exerts a partial non-competitive inhibition; (ii) a stabilizing complex between the catalytic Cys340 and NAD+ is observed and interpreted as a protective mechanism; and (iii) a concerted non-covalent network assists the action of the catalytic residues Cys340 and Glu306. Through mutational analyses of Lys214, Glu306, Cys340, and Glu515 associated with pH studies, we showed that NAD+ binding is controlled by the dyad Lys214-Glu515. Moreover, catalysis is assured by proton transfer exerted by the same dyad networked with the catalytic Glu306, involved in catalytic Cys340 deprotonation/reprotonation. The identification of this weak bond network essential for cofactor binding and catalysis represents a first step to tackling the molecular basis for its deficiency.
CRIS-Team Scopus Importer:2025-01-31
Keywords: bioinformatic and evolutionary analysis; enzymatic mechanism; kinetics; succinic semialdehyde dehydrogenase; succinic semialdehyde dehydrogenase deficiency